دراسة عوامل توافق نظم المعلومات المحاسبية "دراسة ميدانية على عينة من الشركات الصناعية السورية" - ابراهيم, علي كامل; داؤد, هزار سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يشكل نظام المعلومات المحاسبية نظامًا فرعياً ضمن نظام المعلومات المتكامل في الوحدة الاقتصادية يتطلب منه التنسيق والتكامل مع نظم المعلومات الفرعية الأخرىفيها, ويتوجب عليها لاهتمام بالاختيار المحاسبي السليم والدقيق للمعلومات, والتدفق المناسب للمعلومات من خلال توفير مخرجات لا تتضمن محتوى واحداً, وإنما تتوافق مع احتياجات المستخدمين للمعلومات. يتناول البحث الحالي دراسة تأثير مجموعة من العوامل المحتملة وهي (تقدم تكنولوجيا المعلومات, ومستوى معرفة المدير أو المالك بالمحاسبة وتطبيقات تكنولوجيا المعلومات, ومدى الاستعانة بخبرات داخلية وخارجية, وحجم الشركة, ودراسة متطلبات المستخدم في مرحلة تصميم النظام) على توافق نظم المعلومات المحاسبية في الشركات الصناعية السورية. وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: - إن الشركات التي تستخدم تكنولوجيا معلومات أكثر تقدماً تميل إلى تحقيق درجة عالية من التوافق في نظم المعلومات المحاسبية. - إن الشركات التي يملك مديروها مستويات عالية من الالتزام تميل إلى تحقيق درجة عالية من التوافق في نظم المعلومات المحاسبية. - إن الشركات التي تشرك خبرة داخلية وخارجية تميل إلى تحقيق درجة عالية من التوافق في نظم المعلومات المحاسبية. - إن الشركات التي لديها عدد أقل من الموظفين (حجمها أقل) تميل إلى تحقيق درجة عالية من التوافق في نظم المعلومات المحاسبية. - إن الشركات التي تهتم بدراسة متطلبات المستخدمين في مرحلة تصميم النظام تميل إلى تحقيق درجة عالية من التوافق في نظم المعلومات المحاسبية. Accounting information system forms a subsidiary subsystem within the integrated information system in the economic entity requiring coordination and integration within information systems of other subsidiary subsystems. It is of great concern to make a proper choice concerning accurate, accounting information and adequate flow of information through the provision of outputs containing more than one content, and consistent with users' need of information . This research addresses the impact of a range of possible factors, namely advances in information technology, the level of the manager's or owner's accounting knowledge of, information technology applications, the use of internal and external expertise, the size of the company, and finally the study of the user's requirements in the phase of system design, on the compatibility of accounting information systems in industrial companies of Syria. After doing the research and analysis, we have reached the following results: - Companies that use more advanced information technology tend to achieve a high degree of consistency in accounting information systems. - Companies whose managers have high levels of commitment tend to achieve a high degree of consistency in accounting information systems. - Companies that engage internal and external experience tend to achieve a high degree of consistency in accounting information systems. - Companies that have a smaller number of employees (size less) tend to achieve a high degree of consistency in accounting information systems. - Companies that are interested in studying the user's requirements in the phase of system design tend to achieve a high degree of consistency in accounting information systems.